Alat Uji Data Tahan Mekanik dan Elektrik Untuk "Mobiya" Menggunakan PLC - Lisa Eka Putri Utami; Rizky Pratama Hudhajanto (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
Portable lights are electronic devices that can be used practically anywhere. They are manufactured to be sold to countries where access to electricity is difficult, such as countries in the African continent. One of these products is called "Mobiya", a rechargeable battery-powered portable lamp. The recharging process uses a DC power source with a Universal Serial Bus (USB) type power inlet. This article discusses the creation of a test tool to control the quality of Mobiya portable lamp production. The creation of this tool includes the process of designing, manufacturing, and testing. In addition, Preventive Maintenance is also presented in the form of statistical data processing to obtain the status and condition of the test equipment as a basis for maintenance. This study succeeded in creating a test tool capable of testing Mobiya portable lamps in accordance with production standards.